Benign Recurrent Intrahepatic Cholestases - Femmy Nurul Akbar; Sjaifoellah Noer; L A Lesmana; Unggul Budihusodo; Wirasmi Marwoto (The Indonesian Society for Digestive Endoscopy, 2001)
Benign recurrent intrahepatic cholestasis (BRIC) or idiopathic recurrent intrahepatic cholestasis is a rare case. It is a familial and autosomal recessive. The etiology of BRIC is still unknown. We report the case of a patient with BRIC who suffered from recurrent jaundice 7 times in 7 years that occurred for 1-3 months with spontaneous resolutieon. This patient received ursodeoxycholic acid, cholestiramine and prednisone. And within 2 months, the jaundice resolved together with other complaints. Keywords: cholestasis, autosomal, familial